From a Worldview Perspective: Empowering Indonesian EFL Educators’ Professionalism through Self-Efficacy - Wijaya, Kristian Florensio (Indonesian Journal of Integrated English Language Teaching, 2024)
AbstractIn an educational milieu, professional EFL educators oftentimes bear a huge responsibility for becoming agents of change toward the promotion of better-quality language learning processes. Concerning this matter, the immediacy of corroborating EFL educators’ self-efficacy is considered crucially important since they believe in their existing competencies to accomplish the demanding working loads given by educational institutions. This present small-scale qualitative library study was an apparent attempt to signify the critical role of self-efficacy to be activated at the beginning of Indonesian EFL teachers’ teaching careers. To fulfill this main study purpose, 25 previously-related EFL teachers’ self-efficacy studies were selected to shed enlightenment for our educational stakeholders to start prioritizing their teachers’ significant self-efficacy development to promote more holistic language learning enterprises for learners. To ensure the eligibility and relevancy of reviewed research results, the researcher also employed a thematic analysis. There were two major specific themes yielded from an in-depth thematic analysis namely: (1) Highly self-efficacious EFL educators can potentially promote a conducive-friendly classroom climate and (2) the robust growth of self-efficacy progressively transfigures EFL educators into more persistent figures. From these two subdivided themes, it was implied that through the constant elevation of self-efficacy, EFL educators will be more professional initiators who are successful in terms of promoting positively-sound learning vicinities and preserving their best working performances amidst various educational complexities.        Keywords: Professionalism, Self-Efficacy, EFL Teachers, Library Study